Harvests in Sweden before the agrarian revolution - Hallberg, Erik; Linde, Martin; Leijonhufvud, Lotta; Andersson Palm, Lennart (University of Gothenburg, 2017)
Grain tithe (Swe: Spannmålstiondet) has often been used as an indicator of crop development. It was a tax based in the principle of one-tenth of the harvest. This database is based on the accounts of the Crown's share of the tithe for Sweden in present-day borders excluding Scania. The databases relate to the period from and including 1665, when the volume measures were uniform in the country, until the tithe was a fixed tax without further linked to harvests. The transition to the tenth occurred successively in different provinces and was essentially completed by the mid-1700s.

Spannmålstiondet har ofta använts som indikator på skördeutvecklingen, det utgick ju i princip med en tiondel av skörden. Föreliggande databaser bygger på räkenskaper över kronans andel av tiondet för Sverige inom nutida gränser exklusive Skåne. Databaserna avser tiden fr o m 1665, då volymmåtten blev enhetliga i landet, tills tiondet blev en fast skatt utan vidare anknytning till skördarna. Övergången till fast tionde skedde successivt i olika landskap och var i huvudsak avslutad vid 1700-talets mitt.
Skördar i Sverige före agrarrevolutionen
Keywords: population; befolkning; agriculture; lantbruk; farming; jordbruk; Early modern period; tidigmodern tid; 17th century; 1600-tal; 18th century; 1700-tal; HISTORY; HISTORIA; Probability Theory and Statistics; Sannolikhetsteori och statistik; Agricultural and Veterinary sciences; Lantbruksvetenskap och veterinärmedicin; Agricultural Science; Jordbruksvetenskap; History and Archaeology; Historia och arkeologi; History; Historia